Basic Investigation of COVID-19's Self Isolation Room in Various Residential Typology - Anggana Fitri Satwikasari; Erni Setyowati; Norhayati Mahyuddin; Jundi Jundullah Afghani; Evi Puspitasari; Yudi Kurnia (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
The self-isolation room, is one of the main additional re-adjusting plan for the family who have the COVID-19 infected member, especially for those who get medical recommendation for staying at their homes, instead of being treated in the medical facilities. Isolation is a different from the term of quarantine. People who is decided to be isolated is the one who tested positive COVID-19 and strictly have to be separated from the others. Meanwhile, a quarantine is a 14-days limitation access for the healthy people who have close contact with the infected person. This research aim to gather and analyze the existing data of the isolation room’s technical criterias on the COVID-19 Survivors’ houses. The collecting data process were using questionaire method that referred to the protocol’s 10 parameters related to architecture in the Indonesian Ministry of Health’s Community-Based Shelter Facilities for Quarantine and Isolation Protocol During the Covid-19 Pandemic [1]. The collected data will be analyzed and presented in bar chart as the visualization of the distributive analysis for each parameters. The sample houses will be classified into 4 categories based on their house are, which would be the category 1 (9 m2), category 2 (9,1-50 m2, category 3 (50,1-100 m2), and category 4 (> 100 m2).